KARAKTERISTIK DAN PERILAKU LOVEBIRD JANTAN SERTA BETINA SPESIES Agapornis fischeri VARIAN HIJAU STANDAR - Dina Sari Dewi; Tintin Kurtini; Rr Riyanti (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The purpose of this research was identify the characteristics and behaviour of males and females lovebird species Agapornis fischeri of standard green variant. The research has been conducted in February till April 2015 in the lovebird breeding room’s on the Senopati street of Jatimulyo village, Jati Agung, South Lampung. The object being observed are five pairs of lovebird who have reached sexual maturity (≥9 months). The males and females of body weight obtained through scale digital after behaviour observation and fasted it first. The result were analyzed using chi-square method with level of 5% on the characteristics and focal animal sampling method to behaviour observated via video camera for six days in each cage object. Assessment of characteristics lovebird observed are body shape, head shape, and tail feather shape while the observation of behaviours were ingestive (eating, drinking, and cleaning beak), idle behaviour (perching and resting), and sexual behaviour (approaching females, delouse, flirting, and mating). The result of this research showed difference nonsignificant (P>0.05) between of males and females lovebird on the characteristics. The average percentage of lovebird behaviours were drinking, cleaning up of beak, perching, approached females, and delouse behaviour in males larger than females. Otherwise, the average percentage of lovebird behaviours were eating, resting, and flirting behaviour in females larger than males. Keywords: Lovebird Agapornis fischeri, variant, gender, characteristics, and behaviours